Probing the relative importance of different attributes in L2 reading and listening comprehension items: An application of cognitive diagnostic models. (July 2017) - Yi, Yeon-Sook
The present study examines the relative importance of attributes within and across items by applying four cognitive diagnostic assessment models. The current study utilizes the function of the models that can indicate inter-attribute relationships that reflect the response behaviors of examinees to analyze scored test-taker responses to four forms of TOEFL reading and listening comprehension sections. The results are interpreted to determine whether the subskills defined in each subtest contribute equally within an item and across items. The study also discusses whether the empirical results support the claims for compensatory processing of L2 comprehension skills and presents practical implications of the findings. The article concludes with the limitations of the study and suggestions for future research.